Pengukuran Reliabilitas Menggunakan Pearson Correlation Pada Technique For Order Preference by Similarity of Ideal Solution (TOPSIS) - Murtina, Hidayanti (INFORMATION MANAGEMENT FOR EDUCATORS AND PROFESSIONALS : Journal of Information Management, 2018)
Abstrak : Telah banyaknya metode penunjang keputusan yang ada membuat penentuan dalam pemilihan sebuah metode untuk membantu dalam pengambilan keputusan menjadi cukup membingungkan, dikhawatirkan metode yang telah dipilih tidak cukup tepat untuk membantu menyelesaikan masalah atau menghasilkan nilai yang kurang baik. Sehingga banyak keputusan yang diambil dengan cara manual, salah satunya adalah pemilihan calon supervisor yang menerapkan sistem kalkulasi dan gugur. Untuk itu penulis melakukan pembuktian dengan melakukan perhitungan nilai reliabilitas dengan pendekatan metode Pearson Correlation dari kasus pemilihan supervisor menggunakan metode TOPSIS yang sudah dilakukan di penelitian sebelumnya. Dan hasil yang didapat dari pembuktian ini adalah metode TOPSIS dinilai sangat layak untuk dapat digunakan membantu pengambilan keputusan pemilihan supervisor karena memiliki nilai pengujian reliabilitas senilai 0,9932 dari maksimal nilai reliabilitas adalah 1.   Kata kunci: pearson correlation , pengujian reliabilitas, TOPSIS   Abstract:   Has many method supporting decision that is make the determination of in an election a method of to assist in decision-making be quite confuse, It was feared that a method of that has been chosen not quite exact to help put the finishing touches to a problem or produce values to a less well. To execute so that many the decision taken use manual system, One of these is the the election of a candidate supervisor who have applied a system calculations and did not qualify. For that writer do of by doing calculation of the value of reliability with the approach method Pearson Correlation from the case of the election supervisor uses the method topsis who has been done in previous studies. And the outcomes which be gleaned from this kind of proof is a method of topsis considered to be very worthy to can be used help over the withdrawal of funds the decree of election supervisor because having the value of the testing proposed senior unsecured bonds programme reliabilisa 0,9932 from a maximum of reliability value is 1.   Keywords : pearson correlation, reliability testing, TOPSIS